8C.04: POSSIBLE ROLE OF ARTERIAL FUNCTION IN CANCER TREATMENT TARGETING VASCULAR ENDOTHELIAL GROWTH FACTOR RECEPTOR ONCOLOGIC RESPONSE. (June 2015) - Vallerio, P.; Stucchi, M.; Moreo, A.; Ricotta, R.; Pozzi, M.; Giupponi, L.; Cazzaniga, M.; Meani, P.; Varrenti, M.; Facchetti, R.; Di Bella, S.; Giganti, M.O.; et al.
Abstract : Objective: In the last two decades new drugs that oppose the effects of vascular endothelial growth factor receptor (VEGFR), and thus angiogenesis, have considerably improved treatment of solid tumors. These anti-VEGFR drugs, however, are burdened by several side effects, particularly relevant on heart and vessels. Aim of this study was to analyze the changes in cardiovascular structure and function associated with use of anti-VEGFR drugs. Design and method: 29 patients (27 affected by renal and 2 by thyroid cancer), received treatment with antiVEGFR drugs. Hemodynamic, non invasive arterial investigation (Pulse Wave velocity -cfPWV-, Augmentation Index-Aix- and Aortic Pressure) and echocardiography with global longitudinal strain (gLS) were performed before starting therapy (T0), after 2 (T1) and 6 weeks (T2). Oncologic outcome was determined by the assessment of the neoplastic lesions at CT scans, according to Response Evaluation Criteria in Solid Tumors Guidelines. Results: A significant increase of both peripheral and central blood pressure (BP) was observed. We documented a significant raise of cfPWV from T0 (9.9 ± 2.5m/sec) to T1 (10.6 ± 2.3m/sec); at T2 cfPWV still increased in patients who continued treatment (10.8 ± 2.3m/sec), while decreased in patients who stopped therapy (9.8 ± 1.9m/sec). At the on-treatment CT scan (available in 22 patients) 12 patients had a stable disease (StD), 5 showed a reduction of the lesions (responders –PR-) and 5 showed a disease progression (PD). PD patients showed a lower cfPWV at T2 than StD-PR patients (cfPWV: 9.3 ± 2.8 Vs 13.3 ± 1.5 m/sec; p value 0.02). Aix at T1 was higher in PD than in StD-PR (Aix: 36 ± 2.8% Vs 24.6 ± 9.2%; p value 0.02). Conclusions: Anti-VEGFR treatment is associated with a marked increase in both brachial and central BP. Moreover it early induces an aortic reversible stiffening. The evidence that cfPWV and AIx changes are early and sensitive cardio-vascular effects of anti-angiogenic treatment and that disease progression is associated with a concomitant come back to pre-treatment value of cfPWV and a further increase in augmentation index, suggests their possible role on oncologic outcome.